Hidrolisis Pati Kacang Kedelai (Glycine max (L.) Merril) dengan Pengaruh Jenis Katalis Asam - Siska Futri Nasution; Lathipah Hannah Lubis; Susilawati Harahap; Azhari Umar Siregar (Journal of Pharmaceutical and Health Research, 2023)
Soybean (Glycine max (L.) Merril) is beneficial for lowering blood sugar, relieving menopausal symptoms and preventing dementia. This study aims to determine the effect of the acid catalyst used on the hydrolysis process of soybean starch (Glycine max (L.) Merril) and to determine the effect of time on the process of hydrolysis process of soybean starch (Glycine max (L.) Merril). There are 3 types of acid catalysts used, namely 0.1 N HCl; H2SO4 0.1N; HNO3 0.1 N. Types of qualitative and quantitative research conducted in the pharmaceutical laboratory of the Institut Teknologi dan Kesehatan Sumatera Utara. The results obtained in this study with 0.1 N HCl acid catalyst type for 4 minutes, 5 minutes, 6 minutes, and 7 minutes obtained successive volumes of 15 mL, 21 mL, 18 mL, and 9 mL. 0.1 N H2SO4 catalyst for 4 minutes, 5 minutes, 6 minutes, and 7 minutes, the volumes obtained were 22 mL, 20 mL, 17 mL, and 14 mL, respectively. 0.1 N HNO3 catalyst for 4 minutes, 5 minutes, 6 minutes, and 7 minutes, the volumes obtained were 24 mL, 20 mL, 17 mL, and 13 mL, respectively. From the research results, we can find out the optimal volume produced in 7 minutes with 0.1 N HCl acid catalyst. The longer the time used for hydrolysis process in soybean starch (Glycine max (L.) Merril), the smaller the average volume produced.